2019
DOI: 10.1158/1078-0432.ccr-18-2291
|View full text |Cite
|
Sign up to set email alerts
|

Developing Allogeneic Double-Negative T Cells as a Novel Off-the-Shelf Adoptive Cellular Therapy for Cancer

Abstract: Purpose: To expand clinical-grade healthy donor-derived double-negative T cells (DNT) to a therapeutically relevant number and characterize their potential to be used as an "offthe-shelf" adoptive cellular therapy (ACT) against cancers.Experimental Design: We developed methods to expand DNTs under GMP conditions and characterized their surface molecule expression pattern using flow cytometry-based high-throughput screening. We investigated the off-the-shelf potential of clinical-grade DNTs by assessing their c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 53 publications
(74 reference statements)
2
80
0
Order By: Relevance
“…Previous reports have demonstrated that DNT cells have significant anti-cancer effects in patient-derived xenograft (PDX) models of lung cancer and leukemia (9)(10)(11)(12). Moreover, infusion of allogeneic DNT cells did not induce graft versus host disease (13). These unique features of DNT cells differentiate them from conventional T cells and support their potential use as a new adoptive cellular therapy for cancers (13).…”
mentioning
confidence: 80%
“…Previous reports have demonstrated that DNT cells have significant anti-cancer effects in patient-derived xenograft (PDX) models of lung cancer and leukemia (9)(10)(11)(12). Moreover, infusion of allogeneic DNT cells did not induce graft versus host disease (13). These unique features of DNT cells differentiate them from conventional T cells and support their potential use as a new adoptive cellular therapy for cancers (13).…”
mentioning
confidence: 80%
“…NKG2D mediates cytotoxicity by combining MHC class I polypeptide-related sequence A and B with UL16-binding protein molecules, which are highly expressed on tumor cells [62,78]. DNAM-1 induces killing by recognizing CD112 and CD155 ligands, which are highly expressed on tumor cells but negligibly expressed on their normal counterparts [68,[79][80][81][82][83][84][85][86]. Lee J et al [36] demonstrated that DNTs recognize and kill acute myeloid cells mainly by activating NKG2D and DNAM-1 receptors.…”
Section: Ligand-receptor Bindingmentioning
confidence: 99%
“…The isolation and expansion of DNTs in vitro could prevent the activation of various immunosuppressive mechanisms in the tumor microenvironment. Lee JB and coworkers [86] established a system to expand clinically applicable DNTs derived from healthy volunteers ( Figure 1); specifically, they used cytokines to mediate the activation and proliferation of the DNTs in vitro, thereby preventing serious side effects caused by the application of biological agents in vivo. Infusion of allogeneic DNTs does not cause GVHD [112][113][114], and DNTs can kill cancer cells but are harmless to normal cells.…”
Section: Advantages Of Dntsmentioning
confidence: 99%
See 2 more Smart Citations